2021
DOI: 10.1021/acs.joc.1c00857
|View full text |Cite
|
Sign up to set email alerts
|

The Ligand Free Palladium(II)-Catalyzed Regioselective 1,2-Addition of Enol Silanes to Quinones to Access 4-Hydroxy-4-(2-oxo-2-arylethyl)cyclohexadien-1-ones and Synthetic Applications

Abstract: In contrast to the conventional 1,4-addition process, regioselective 1,2-addition of silyl enol ethers to quinones can now be achieved via a palladium­(II) enolate pathway that provides access to 4-hydroxy-4-(2-oxo-2-arylethyl)­cyclohexa-2,5-dien-1-one derivatives. This quinone alkylation protocol proceeds under mild reaction conditions at ambient temperature under open air and does not require either an external ligand for the palladium or the use of a base. Additionally, the cyclohexadienone products have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…[20][21][22] Taking advantage of the unique function of silyl enol ethers as masked enolate precursors of ketones, aldehydes and esters, the development of numerous synthetic protocols involving the construction of new C-C, C-N, C-O, C-S and C-x (x = halogen) bonds has been reported over the last three decades. [23][24][25][26][27][28][29][30][31][32] Specifically, silyl enol ethers serve as the preferred reagents to generate enolate equivalents in a regio-and stereo-selective manner, which has empowered their utility as versatile synthetic intermediates in the construction of building blocks of interest to pharmaceutical chemistry to generate diverse scaffolds and drug-like compounds for a range of therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Taking advantage of the unique function of silyl enol ethers as masked enolate precursors of ketones, aldehydes and esters, the development of numerous synthetic protocols involving the construction of new C-C, C-N, C-O, C-S and C-x (x = halogen) bonds has been reported over the last three decades. [23][24][25][26][27][28][29][30][31][32] Specifically, silyl enol ethers serve as the preferred reagents to generate enolate equivalents in a regio-and stereo-selective manner, which has empowered their utility as versatile synthetic intermediates in the construction of building blocks of interest to pharmaceutical chemistry to generate diverse scaffolds and drug-like compounds for a range of therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that Pd­(II) enolates derived from enol silane substrates are able to function as efficient nucleophiles that can add regioselectively to the carbonyl carbon of quinones in a 1,2-addition fashion to access 4-hydroxycyclohexadien-1-one derivatives . Inspired by this, we examined a range of Pd­(II) or Pd(0)-based catalysts starting with Pd­(OAc) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that Pd(II) enolates derived from enol silane substrates are able to function as efficient nucleophiles that can add regioselectively to the carbonyl carbon of quinones in a 1,2-addition fashion to access 4-hydroxycyclohexadien-1-one derivatives. 39 Inspired by this, we examined a range of Pd(II) or Pd(0)-based catalysts starting with Pd(OAc) 2 . However, our attempts with Pd-(OAc) 2 as the catalyst precursor in the presence of solvents like DMF, NMP, and MeCN met with a dismal formation of the desired product (0−5% yield), with the observation of decomposition of 2a to its parent ketone 4a as the major pathway (Table 1, entries 4−6).…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 99%
“…The limited number of existing methods to transform saturated ketones to β-aryl enones and the limitations associated with these protocols spurred us to design and develop an alternative approach based on a retrosynthetic strategy relying upon silyl enol ethers as substrates, taking advantage of their function as masked enol equivalents of saturated ketones (Scheme ). In the forward synthetic direction, enol silanes would be expected to fulfill the role of acting as synthetic equivalents of saturated ketones by undergoing dehydrosilylation with the in situ generation of α,β-unsaturated ketones that would then be arylated in a one-pot process. We were particularly interested in exploring silyl enol ethers as versatile reagents in a continuation of our earlier research that took advantage of their nucleophilic character to enable C–C and C–N bond formation with quinone, carbodiimide, and azodicarboxylate electrophilic systems. Importantly, silyl enol ethers (a) are readily prepared from keto, aldehyde, and ester precursors; (b) are the reagents of choice for the regio- and stereo-selective generation of enolate equivalents; (c) undergo a diverse range of synthetic reactions, including aldol condensations, Michael additions, and [4 + 2] cycloadditions; and (d) find use as synthetic building blocks in pharmaceutical chemistry to generate drug-like compounds of diverse architecture. Herein, we report for the first time the synthesis of β-arylated enone derivatives from enol silanes through the sequential generation of an enone in situ and the ensuing arylation with arylboronic acids or aryl halides in a convenient, one-pot process using modular Pd­(II)/Pd(0) catalytic systems (Scheme , eq 3).…”
Section: Introductionmentioning
confidence: 99%